Wear Prediction and Chaos Identification of Rigid Flexible Coupling Multi-Link Mechanisms with Clearance - Yonghao Jia; Kai Meng; Shuai Jiang; Jing Kang (Lubricants)
Traditional revolute clearance joints assume that the shape of the contact surface of the joint is regular and ignores the effects of wear, which reduces the prediction accuracy of dynamics models. To accurately describe the collision behavior of the motion pair, an Archard formula was applied to construct a wear clearance model. Based on the absolute node coordinate method, multi-body dynamics modeling, wear prediction, and chaotic identification analysis methods for a flexible multi-link mechanism with clearance considering wear effects were proposed. The research results indicate that wear exacerbates the irregularity of the clearance surface contours, leading to increased instability in the dynamic response and the reduced motion accuracy of the mechanism. Compared with clearance size, driving speed has a more significant impact on the chaotic behavior of the system. For high-speed conditions, maintaining the clearance size within approximately 0.1 mm is beneficial for system stability, although this requirement poses challenges for cost control in manufacturing. This study provides a theoretical foundation for wear prediction and stability optimization of high-precision multi-link mechanisms.